CMET-22. CAPMATINIB (INC280) IN METΔEX14-MUTATED ADVANCED NON-SMALL CELL LUNG CANCER (NSCLC): EFFICACY DATA FROM THE PHASE 2 GEOMETRY MONO-1 STUDY. (11th November 2019) - Heist, Rebecca S; Seto, Takashi; Han, Ji-Youn; Reguart, Noemi; Garon, Edward B; Groen, Harry J M; Tan, Daniel S W; Hida, Toyoaki; de Jonge, Maja; V Orlov, Sergey; Smit, Egbert F; Souquet, Pierre-Jean; et al.
Abstract: BACKGROUND: Capmatinib is a highly potent, selective MET-inhibitor known to cross the BBB, and intracranial activity with capmatinib has been previously reported. Updated results for overall response rate (ORR), duration of response (DOR), progression-free survival (PFS), and brain metastases (BM) activity from the GEOMETRY mono-1 study are presented here. METHODS: GEOMETRY mono-1 is a phase 2, multi-cohort, multicenter study evaluating capmatinib in MET Δex14-mutated or MET -amplified NSCLC patients. Patients (≥18 years) with ECOG PS 0–1, ALK-/EGFR -wt, and stage IIIB/IV NSCLC were eligible. Patients with asymptomatic BM were allowed. MET Δex14-mutated patients were assigned to Cohorts 4 (1–2 prior lines of treatment) and 5b (treatment-naive) and received capmatinib 400mg BID. Endpoints by BIRC: ORR (primary, RECIST v1.1), DOR, and PFS. Ad hoc BIRC neuro-radiologic assessments of all Cohort 4 and 5b patients with baseline BM were performed. RESULTS: As of April 15, 2019, 97 patients (Cohort 4: 69 patients; Cohort 5b: 28 patients) were evaluable for efficacy. BIRC assessments: ORR (95%CI): 40.6% (28.9–53.1) in Cohort 4; 67.9% (47.6–84.1) in Cohort 5b. Median DOR (95%CI): 9.7 (5.55–12.98) and 11.1 (5.55-NE) months and median PFS (95%CI): 5.4 (4.17–6.97) and 9.7 (5.52–13.86) months for Cohorts 4 and 5b, respectively. Of 13 evaluable patients with BM at baseline, 7 (54%) had intracranial response by BIRC, including 4 patients with complete resolution of brain lesions, and 12/13 had intracranial disease control. Responses in the brain were as fast as systemic responses. Most common treatment-related AEs (≥15%, all grades) across all cohorts (N=334): peripheral edema (41.6%), nausea (33.2%), increased blood creatinine (19.5%), and vomiting (18.9%); most AEs were grade 1/2. CONCLUSION: These data confirm capmatinib to be a promising new treatment option for patients with METΔex14 -mutated advanced NSCLC regardless of line of therapy, with deep and durable responses including in patients with brain metastases, and a manageable toxicity profile.